The Evangelization of Korea, c.1895–1910: Translation of the Gospel or Reinvention of the Church? - Kim, Kirsteen (Studies in church history, 2017)
Several studies of the history of Protestant Christianity in South Korea have argued that the religion's rapid growth was chiefly because of the successful translation of the gospel into Korean language and thought. While agreeing that the foundation laid in this respect by early Western missionaries and Korean Christians was a necessary prerequisite for evangelization, this article challenges the use of a translation theory, such as has been developed by Lamin Sanneh, to describe the way that Christianity took root in Korea, both on the basis of conceptual discussions in the field of mission studies and also on historical grounds. It draws on research for A History of Korean Christianity (2014) to examine the years of initial rapid growth in Protestant churches in Korea - 1895 to 1910. Its findings suggest that rather than ‘translation of the gospel’ a more historically accurate description of what took place is ‘reinvention of the Church’.